PENINGKATAN HASIL BELAJAR PEMBELAJARAN IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF DENGAN MEDIA ULAR TANGGA PADA MATERI KEGIATAN PEMANFAATAN SUMBER DAYA ALAM - M, Mukhaloroh; Sudin, Ali; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
Based on preliminary data obtained in the fourth grade of SDN 3 Ender, student learning outcomes on the subject of natural resources utilization activities have some problems related to the teaching and learning process that affect the outcomes achieved by the students when evaluating the result of the less satisfactory / not yet reached the KKM. Because of the less satisfactory value of students due to lack of understanding of students on the material being taught. Efforts to improve the problem is by applying cooperative learning model with Snake Stage media. The problem was corrected through Classroom Action Research (PTK) with design of Kemmis and Taggart model research design. Instruments used include guidelines for student and teacher interviews, teacher performance observation guidelines on planning and implementation, student activities, student learning outcomes, and field notes. This study was completed in III cycles. Thus, it is hoped that Cooperative learning model with Snake Stage media can improve student learning result of class IV, in material of natural resources utilization activity.